2007
DOI: 10.1097/meg.0b013e3282f16251
|View full text |Cite
|
Sign up to set email alerts
|

Resistin is an inflammatory marker of inflammatory bowel disease in humans

Abstract: Resistin levels are an independent predictor of disease activity in patients with CD. Resistin may represent a novel link between inflammation and IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
85
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(96 citation statements)
references
References 24 publications
6
85
0
5
Order By: Relevance
“…Increased serum resistin levels have been detected in both Crohn's disease and ulcerative colitis patients [120,121,122]. In addition, resistin correlated with the disease activity score, white blood cell count, and CRP in patients with Crohn's disease [121,122].…”
Section: Resistin and Inflammatory Bowel Diseasesmentioning
confidence: 96%
See 2 more Smart Citations
“…Increased serum resistin levels have been detected in both Crohn's disease and ulcerative colitis patients [120,121,122]. In addition, resistin correlated with the disease activity score, white blood cell count, and CRP in patients with Crohn's disease [121,122].…”
Section: Resistin and Inflammatory Bowel Diseasesmentioning
confidence: 96%
“…In addition, resistin correlated with the disease activity score, white blood cell count, and CRP in patients with Crohn's disease [121,122]. In contrast to leptin and adiponectin, resistin significantly decreases after TNF-α blocking therapy in patients with inflammatory bowel diseases and has been proposed as a marker of successful therapy, similar to the patients with rheumatoid arthritis [123].…”
Section: Resistin and Inflammatory Bowel Diseasesmentioning
confidence: 97%
See 1 more Smart Citation
“…Resistin in humans appears to have a significant proinflammatory role by targeting PBMCs, endothelial cells, smooth muscle cells, platelets (30), and chondrocytes (31) and by increasing the release of IL-1β, IL-6, and TNF-α via the NF-κB pathway (32). Resistin has been reported to be a marker of inflammation in systemic lupus erythematosus (SLE) and Crohn's disease in humans (33). It is unclear at this time why resistin had this unusual behavior in our study, increasing with mild to moderate disease severity but decreasing with moderate to severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…In adult patients with sepsis, resistin was implicated as an effective biomarker of sepsis severity and as a predictor of mortality of critically ill adult patients. Also, Serum resistin levels were elevated in patients with inflammatory bowel disease and it was correlated with CRP, TLC levels and with the disease activity [16]. In a study done by Adrych et al, they reported that serum-resistin levels were elevated in patients with chronic pancreatitis and they suggested its role in the development of pancreatic fibrosis [17].…”
mentioning
confidence: 94%